Buchwaldoboletus lignicola (Basidiomycetes), an Inedible Wild Mushroom New to Nepal - Aryal, Hari Prasad; Budathoki, Usha (Our Nature, 2013)
The survey of wild mushrooms in tropical to temperate belts of Nepal during the rainy season was conducted in 2012. The Buchwaldoboletus lignicola (Kallenb.) Pilat, which is being reported and redescribed for the first time from Nepal. The habitat of the fungus was subtropical deciduous hill forest between 1030 to 1360 m msl. The dried specimen is deposited in the Tribhuvan University Central Herbarium (TUCH), Kirtipur Kathmandu, Nepal. DOI: http://dx.doi.org/10.3126/on.v11i1.8241 Our Nature Vol.11(1) 2013: 31-35